India in Australia's Strategic Framing in the Indo–Pacific. Issue 2 (4th March 2018) - Thakur, Ramesh; Sharma, Ashok
Abstract: The world is witnessing a geopolitical shift from the North Atlantic to the Indo–Pacific region. US power is in relative decline with a steady build-up of Chinese power, wealth and influence. The last 15–20 years have also seen the rise of India. Against this backdrop, Australia's reconceptualisation of its strategic frame as the Indo–Pacific widens its geopolitical canvas and elevates India's importance for multiple Australian interests and objectives. We analyse India's growing role, with the potential to change the geopolitical map of the Indo–Pacific, in four plots significant to Australia's future in a multiplex regional order.